Reconstructive surgery after Female Genital Mutilation: a multidisciplinary approach - Restaino, Stefano; Pellecchia, Giulia; Driul, Lorenza; Alberico, Salvatore (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Female Genital Mutilations (FMGs) are all interventions involving partial or total removal of external female genital apparatus, perpetrated not for therapeutic purposes. This review aims to describe a multidisciplinary approach to clinical management of women with FGM, requiring reconstructive surgery and therapeutic deinfibulation. Furthermore, these traditional procedures are harmful to women’s physical integrity, being able to result in severe psychological damage with strong inhibitions in sexual and emotive life. Methods: Clinical management followed internal protocol implemented at the obstetric Pathology of IRCCS Burlo Garofolo of Trieste, in the framework of the regional project "Female genital mutilation and women immigrants: a draft integrated training and support person," supported by Regione Friuli Venezia Giulia, Italy. We have enrolled in our protocol 15 women that came in our Hospital spontaneously. Here, we present a case of a 38-year-old woman, who had undergone ritual FGM type III with a deep groove scar. She had suffered pain and limitations to sexual intercourses. Results: We performed a reconstructive surgery of the mutilated genital tissue and a therapeutic deinfibulation. The deep groove scar was successfully removed with a multidisciplinary approach. We achieved careful evaluation, both clinical and psychological, of the patient, before surgery. Conclusions: Reconstructive surgery for women who suffer sexual consequences from FGM is feasible. It restores women’s natural genital anatomy, allowing to improve female sexuality.